Determinants of Labor Productivity in Palm Oil Harvesting, Central Kalimantan - Wandha Atmaja Aji; Heri Setyawan; Indra Kurniawan; Idum Satia Santi (Tropical Plantation Journal, 2023)
Work effectiveness is greatly influenced by organizational development, placement, and use of work. Productivity at work has a big impact on results. This study aims to identify the impact of determinants of labor productivity as an oil palm harvester in oil palm plantations in order to increase knowledge, skills and experience in work. Data on the labor productivity of oil palm harvest was carried out by Purpose sampling of 76 people taken from 6 stagnation in 3 afdeling related to wages and premiums obtained every month. Data analysis using descriptive methods and multiple linear regression. Multiple regression analysis partially shows that education level, number of dependents, and age have no real effect on labor productivity, but length of work does. Simultaneous regression tests show that education level, number of dependents, age, and length of working hours have a significant effect on the labor productivity of oil palm harvests.